EFFECTIVENESS OF THE DIGICARE EDUCATIONAL INTERVENTION IN IMPROVING NURSING AND MEDICAL STUDENTS’ CLINICAL COACHING SKILLS IN VIETNAM AND BANGLADESH: AN EXPLORATORY PRE-POST STUDY - Jorge dos Santos Costa, Paulo (2023)
Coaching has become an important approach to support self-management of patients with non-communicable diseases (NCDs) in healthcare education. Studies conducted in European countries have emphasized the significance of formal coaching training in enhancing the competencies of healthcare students. However, in Southeast Asia, where NCDs pose a serious public health concern, there is a lack of such training opportunities. To address this issue, an exploratory pre and post study was conducted to evaluate the effectiveness of the DigiCare educational intervention in improving clinical coaching skills. Nursing and medical students from six universities in Vietnam and Bangladesh were invited to participate. The intervention included both theoretical and practical classes with interactive methods and home assignments, with a total duration of over 10 contact hours. Pre- and post-intervention assessments were conducted using the Self-Efficacy and Performance in Self-management Support instrument, which was translated and culturally adapted to both countries. Statistical analysis showed a significant improvement in students’ overall competence scores from before (M = 2.6, SD = .67) to after the intervention (M = 3.05, SD = .55), with a medium effect size (p < .001; d = .73). The DigiCare educational intervention appears to be a low-cost and meaningful addition to the curriculum of both nursing and medical universities across countries, with potential benefits in the development of students’ clinical coaching competencies.